A direct forcing immersed boundary method for cavitating flows. (26th July 2021) - Stavropoulos Vasilakis, Evangelos; Rodriguez, Carlos; Kyriazis, Nikolaos; Malgarinos, Ilias; Koukouvinis, Phoevos; Gavaises, Manolis
Abstract: In the current study, an immersed boundary method for simulating cavitating flows with complex or moving boundaries is presented, which follows the discrete direct forcing approach. Although the immersed boundary methods are widely used in various applications of single phase, multiphase, and particulate flows, either incompressible or compressible, and numerous alternative formulations exist, to the best of the authors' knowledge, a handful of computational works employ such methodologies on cavitating flows. The herein proposed method, following previous works of the author's group, tries to fill this gap and to solidify the development of a computational tool of a simple formulation capable to tackle complex numerical problems of cavitation modeling. The method aims to be used in a wide range of applications of industrial interest and treat flows of engineering scales. Therefore, a validation of the method is performed by numerous benchmark test‐cases, of progressively increasing complexity, from incompressible low Reynolds number to compressible and highly turbulent cavitating flows. Abstract : Herein the validation of a discrete direct forcing immersed boundary method for computations of cavitating flows in complex topologies is presented. The method is combined with different numerical solvers and turbulence models to enable the simulation of highly turbulent cavitating flows around solid boundaries, with characteristic examples the flow over a pitching NACA66 hydrofoil, where the influence of model choice is striking, and the cavitation inception inside a diesel injector with needle movement, where the field at zero lift is modeled.